CLOUD COMPUTING DAN KAITANNYA DENGAN DISASTER RECOVERY PLANNING - Emilya Ully Artha; Ema Utami (Seminar Nasional Informatika (SEMNASIF), 2011)
Disaster recovery planning if it is associated with contuinity bussiness plan will be a link with data and information held by an organization or company. If interference occurs, it can paralyze business continuity company. It takes data replication to maintain data availability in the event of a disaster at any time